Faktor-Faktor Yang Berhubungan Dengan Kejadian Bayi Berat Lahir Rendah Di Ruang Nicu Badan Layanan Umum Daerah Rumah Sakit Konawe - La Ode Liaumin Azim; Sulaiman, Eman; Sumera, Syahruddin; Hermin, Siti; Sandryana Nur, Ana Dwi; Darmin, Darmin (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat (LPPM), Institut Teknologi Dan Kesehatan (ITK) Avicenna, 2022)
Background: Low Birth Weight Babies (LBW) are newborns whose birth weight is less than 2,500 grams, regardless of gestational age. NICU room data from January to June 2022 found that the number of neonatal patients treated in the NICU was 154 patients, and 92 cases of LBW. Factors that cause LBW are maternal factors, obstetric factors, infant and placenta factors, and environmental factors. Objective: This study aim to identify the factors associated with the incidence of LBW in the NICU BLUD room at Konawe Hospital. Method: This research is an analytical study with a cross-sectional study design, carried out for 4 weeks, from 29 July 2022 to 29 August 2022 using a questionnaire sheet instrument. The number of samples is 31 people obtained by purposive sampling. Data analysis used the fisher's exact test. Results: From 31 respondents, there was a relationship between maternal and obstetric factors and the incidence of LBW (p=0.001<0.05 and p=0.000<0.05). In addition, the results showed that there was no relationship between infant, placental and environmental factors with the incidence of LBW (p=0.372>0.05 and p=0.452>0.05). Conclusion: Factors associated with the incidence of LBW in the NICU BLUD room at Konawe Hospital are maternal and obstetric factors